Kompetensi Guru dalam Pengelolaan Kelas pada Pembelajaran Tematik Madrasah Ibtidaiyah Lembaga Ketahanan Masyarakat Desa Kalapagunung - Suci Nurul Insani Falaah; Henri Peranginangin; Dadan Mardani (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Based on the concept of education initiated by Ki Hajar Dewantara. Namely, the theory of Ing Ngarso Sung Tuladha, Ing Madyo Mangun Karso, and Tut Wuri Handayani, teacher skills in class management in thematic learning are skills that must be mastered by a teacher in terms of teaching and managing classes which include knowledge, attitudes, and skills in managing class in class IV thematic learning. The method used in this study is a qualitative approach and a case-descriptive research type in which all existing problems will be discussed clearly. Data collection techniques were carried out through interviews, observation, and documentation. The subjects in this study were class IV MI LKMD Kalapagunung teachers. The results of this study indicate that there is a teacher's knowledge of the model and method of managing the class, the teacher is very expressive in applying the principles of classroom management, the teacher can apply how to manage interactions and organize the study space well.